Impact of stereotactic radiotherapy on kidney function in primary renal cell carcinoma: Establishing a dose–response relationship. Issue 3 (March 2016) - Siva, Shankar; Jackson, Price; Kron, Tomas; Bressel, Mathias; Lau, Eddie; Hofman, Michael; Shaw, Mark; Chander, Sarat; Pham, Daniel; Lawrentschuk, Nathan; Wong, Lih-Ming; Goad, Jeremy; et al.
Abstract: Background and purpose: To evaluate renal dysfunction after stereotactic ablative body radiotherapy (SABR) for inoperable primary renal cell carcinoma (RCC) using nuclear medicine assessments. Materials and methods: In a prospective clinical trial, patients received single fraction renal SABR (26 Gy) for tumours <5 cm, or fractionated SABR (3 × 14 Gy) for tumours ⩾5 cm. Global and regional glomerular filtration rate (GFR) was calculated through 51 Cr-EDTA and 99m Tc-DMSA SPECT/CT, respectively, at baseline and post-treatment (14, 90 days and at 1-year). Regional loss in function was correlated to the absolute and biologically effective doses (BED) delivered. Results: In 21 patients the mean (range) tumour size was 48 mm (21–75 mm). The mean ± SD GFR at baseline was 52 ± 24 ml/min. Net change in mean GFR was +0.6 ± 11.3, +3.2 ± 14.5 and −8.7 ± 13.4 ml/min ( p  = 0.03) at 2 weeks, 3 months and 1 year, respectively. For every 10 Gy of physical dose delivered, an exponential decline in affected kidney GFR was observed at 39% for 26 Gy/1 fraction and 25% for 42 Gy/3 fractions. When normalised to BED3Gy, the dose–response relationship for each treatment prescription was similar with a plateau beyond 100 Gy. The R50% conformity index correlated with GFR loss ( p  = 0.04). No patient required dialysis. Conclusions: SABR results in clinically acceptable and dose-dependent renal dysfunction at 1-year. Sparing functional kidney from high-dose regions (>50% isodoses) may help reduce risk of functional loss.